Behavior of cement-stabilized clay reinforced with nylon fiber. Issue 1 (1st February 2012) - Namdar, P.; Estabragh, A.R.; Javadi, A.A.
Abstract : ABSTRACT: A series of experiments were carried out to investigate the behavior of cement-stabilized fiber-reinforced clay with different cement and fiber contents. Three groups of tests were conducted, on: (1) reinforced samples with four different fiber contents (0.5%, 0.75%, 1% and 1.25%); (2) cement-stabilized samples with three different cement contents (5%, 8% and 10%); and (3) cement-stabilized, fiber-reinforced samples with the same fiber contents as the uncemented reinforced samples. Unconfined compression tests (UCT) were carried out on the uncemented samples. These UCT tests were also conducted on the cement-stabilized samples with and without fiber inclusions after 3, 7, 14 and 28 days of curing time. The results indicated that the inclusion of fibers within uncemented and cement-stabilized soil caused an increase in the unconfined compressive strength and axial strain at failure, and changed the brittle behavior of the cement-stabilized soil to a more ductile behavior. It was also shown that the mechanical characteristics of the soil–cement–fiber mixtures are functions of fiber content and curing time.